Common factors and balance sheet structure of major European banks - Roma, Antonio (PSL Quarterly Review, 2012)
This paper explores the relationship between listed European banks' fundamental characteristics and the riskiness of their stock returns. Banks' structural characteristics are measured through a number different balance sheet indicators which are then associated to the stock riskiness, as measured by the factor loadings on fundamental factors affecting the stock market at large. The results seem to indicate that, in the 1999-2002 period, in which the banks considered were traded in Euro, the factor loading against the market factor and against the default spread may be systematically related to banks' fundamental characteristics like asset quality indicators (especially reserves for bad loans over loans), to the composition of income (share of interest and commission revenue), and to a general indicator of bank efficiency such as the cost-income ratio. These results are broadly consistent with an option-based theory of bank valuation, which would predict more variability in the price of bank stocks whenbanks hold riskier assets and economic conditions are poor. JEL Codes: G10, G21, L25, M41